The Effectiveness of Internet Marketing in Increasing the Reach and Awareness on Consumer in Bahrain - Hussain Almutawa (International Journal of Engineering and Management Research, 2021)
The present research seeks to expound the effective of Internet marketing in increasing the read and awareness of consumers. Impatient the research conducted a good review about the privies literature related to the study. It leads a brief idea of the study before articulating the statement of the problem. From the statement of the problem deducting the researcher found that the social media , mobile apps and internet marketing have Promina impact with the effectiveness and in cornering the awareness of the consumer .hence the research subdivided the research problem into four different objective such translates the formation of the study states that these is no significant relationship between level of effectiveness and level of utilization of internet marketing on consumer in kingdom of Bahrain . Further the research employs multiple methodologies to a new conclusion on the particular issue, the study used convening sampling method combined with the spss software for data analyse. The study aims to assess the Effectiveness of Internet in Business to increase reach and awareness among consumers in Bahrain. Data and correspondence innovation has changed quickly in the previous 20 years with a key advancement being the development of online networking. Business, which does not utilize internet-based life, tends to lose on key client base. The rise of social media means it’s unusual to find an organization that does not reach its customers and prospects through one social media platform or another. Companies see the importance of using social media to connect with customers and build revenue. Businesses have realized they can use social media to generate insights, stimulate demand, and create targeted product offerings. This is important in traditional brick-and-motor businesses, and, obviously, in the world of e-commerce. In this research, to adequately address the research questions a variety of data collection methods and instruments were used such as questionnaire survey and t-test. From the study, the researcher concluded that there is no significant relationship between the Level of utilization & Effectiveness of Internet marketing among consumers in Bahrain. Therefore, the researchers accept the null hypothesis. The problems faced by the respondents on the Level of utilization & Effectiveness of Internet marketing among consumers in Bahrain is privacy, censorship and online security. The Internet, social media, online advertising, mobile apps etc. as a whole, can be seen as technology that has greatly enhanced our lives but should be done responsibly.